Effectiveness of eLearning programme for capacity building of healthcare professionals: a systematic review - Gifty Francisca Ben Aryee; Mustapha Amoadu; Paul Obeng; Hammond Nii Sarkwah; Ebenezer Malcalm; Susanna Aba Abraham; Jones Abekah Baah; Dorcas Frempomaa Agyare; Nartey Edmond Banafo; Daprim Ogaji (BMC, 2024)
Abstract Background The effectiveness of eLearning in enhancing healthcare professionals' capacity has received substantial attention globally. This review sought to synthesis evidence on the effectiveness of various types of eLearning programmes, and the facilitators and barriers to its use. Methods The review was guided by Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Four main databases (PubMed, Web of Science, JSTOR, and Scopus) in July 2023 and 44 articles met the eligibility criteria and were included in the review. The JBI critical appraisal checklist was used to appraise the methodological quality of the studies. The data were examined using narrative review to determine the effectiveness of the intervention as well as the barriers and facilitators to its use. Results This review found that asynchronous, synchronous, blended, and self-learning methodologies are effective eLearning approaches for continuous professional development. Previous positive experiences, user-friendly interfaces and relevance of the eLearning content to daily practice are critical elements that facilitate eLearning usage. Poor computer competence and literacy, lack of personal computers and high family duties were the main personal factors that hindered eLearning use. Some systemic barriers included; heavy workloads, shortage of specialised eLearning facilitators poor management involvement, and technical inadequacies within the ICT departments. Environmental issues such as poor infrastructure, including limited internet and frequent power outages acted as barriers. Conclusion The review highlights the effectiveness of various eLearning approaches among health professionals and presents the disparities between developing and developed economies in relation to the facilitators and barriers.